1996
DOI: 10.1093/bja/77.6.795
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of laparoscopy for resection of phaeochromocytoma

Abstract: We describe two patients who underwent resection of phaeochromocytoma by a laparoscopic approach. Although outcome from surgery was successful, there was marked variability in hormonal and haemodynamic changes. In one patient, despite an infusion of nicardipine, peritoneal insufflation produced a marked increase in catecholamine concentrations associated with transient but intense vasoconstriction, but there was no change in the second patient. In both patients, exsufflation caused no significant haemodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 15 publications
0
24
0
1
Order By: Relevance
“…α blockade with phenoxybenzamine in increasing doses and preoperative volume expansion is used as standard treatment [10]. Preparation over an adequate period (2 weeks) minimizes hemodynamic changes at induction and intraoperatively [11]. Selective use of β blockade is warranted mostly in adults with documented tachyarrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…α blockade with phenoxybenzamine in increasing doses and preoperative volume expansion is used as standard treatment [10]. Preparation over an adequate period (2 weeks) minimizes hemodynamic changes at induction and intraoperatively [11]. Selective use of β blockade is warranted mostly in adults with documented tachyarrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…After induction of general anesthesia (fentanyl with rocuronium), endotracheal intubation, and placement of an arterial line, urinary catheter, and nasogastric tube, the patient was placed in the right lateral decubitus position (45°).The patient was started on a combination of esmolol (25 μg/kg per minute), phentolamine (1.2 mg bolus prn), and nitropruside (2 μg/kg per hour) drips, with a norepinephrine and epinephrine on standby [10,11]. A 5-mm infra umbilical port was placed using the open technique.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The removal of a pheochromocytoma is associated with specific risks, particularly the occurrence of hypertensive crises, which develop in 50% to 67% of patients because of increased catecholamine levels during the dissection of the tumor and the adrenal gland [9, [20][21][22]. To avoid the development of hypertensive crises, ligation of the adrenal vein before dissection of the organ has been recommended by various authors [10,13,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Various investigators have, however, reported comparable CO 2 absorption values for the retroperitoneal and transperitoneal procedures. The fact that the tendency to acidosis increases with prolonged operating times advocates the selection of the procedure with the shorter operating time [2,7,20].…”
Section: Discussionmentioning
confidence: 99%
“…Insufflation of pneumoperitoneum is associated with an increase in serum catecholamines, either by stimulus to mechanical compression or a change in tumor vascularization (11,12). Additionally, carbon dioxide used to insufflate the pneumoperitoneum can lead to hypercapnia, which would increase sympathetic tonus, thus changing tension levels (13).…”
Section: Commentsmentioning
confidence: 99%